From the repatriation to the exodus of scientists in Argentina - López Monrroy, Ester Elizabeth (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2017)
The Argentine scientific community feels like Sisyphus these days, because the ingenuity would be condemned to push eternally to the top of the mountain, from where the stone returns irreparably to fall. The gods thought that there should be no more terrible punishment than useless labour, so the effort would fail to transfer to society. The impact of the decision is even more profound than if it were only a question of dividends, because without Science there will be no Technology, much less Industry. For this reason, it is difficult to understand how the present management intends to insert the country in a knowledge-based world.